Crise política e referendo popular: o escândalo do mensalão como contexto político-midiático do referendo do desarmamento - Gomes, Maria Lucia Prandi (2007)
On October, the 23rd, 2005, took place in Brazil the Referendo do Desarmamento (Referendum for the Disarmament), when Brazilians voted in favor or against the following question: The fire weapons and ammunitions trade must be prohibit in Brazil? . Polls predicted the vote Yes would win. It lost. The answer No got 63.9% of the total votes. The trade of weapons and ammunitions goes legally on. Different social scientists have studied the Referendo and pointed reasons for the victory of No, which make a complex explanation: the different quality of the radio and TV adverstising of the two sides; the failing of the governmental politics for public security; the lost of credibility of politicians, political parties, particularly the PT, Partido dos Trabalhadores (Workers Party), the federal government and President Luiz Inacio Lula da Silva himself; at last but not least, the weakening of the voters confidence on public institutions because of the crisis that proceeded the Referendo. From May to September, a big scandal called Escândalo do Mensalão (The Big Monthly Bribe Scandal) shook and startled Brazil, affecting negatively the images of President Lula, his government and his Party. The present work seeks to understand the Escândalo do Mensalão as a political background to the Referendum. To reach that aim, two of the most important Brazilian weakly magazines, Veja and Época, were submitted under a content analysis. Both had a similar critical position about the crises of Mensalação, but Veja was in favor of the vote No to the Disarmament, and Época in favor of Yes